As long as we both shall live : a novel - Chaney, JoAnn (New York : Flatiron Books, 2018)
"What happens when you're really, truly done making your marriage work? You can't be married to someone without sometimes wanting to bash them over the head... As Long As We Both Shall Live is JoAnn Chaney's wicked, masterful examination of a marriage gone very wrong, a marriage with lots of secrets... "My wife! I think she's dead!" Matt frantically tells park rangers that he and his wife, Marie, were hiking when she fell off a cliff into the raging river below. They start a search, but they aren't hopeful: no one could have survived that fall. It was a tragic accident. But Matt's first wife also died in suspicious circumstances. And when the police pull a body out of the river, they have a lot more questions for Matt. Detectives Loren and Spengler want to know if Matt is a grieving, twice-unlucky husband or a cold-blooded murderer. They dig into the couple's lives to see what they can unearth. And they find that love's got teeth, it's got claws, and once it hitches you to a person, it's tough to rip yourself free. So what happens when you're done making it work?" --
Keywords: Married people -- Fiction; Wives -- Death -- Fiction; Husbands -- Psychology -- Fiction; Family secrets -- Fiction; Homicide investigation -- Fiction; Mystery fiction; Psychological fiction